NIMG-47. METABOLIC CHARACTERIZATION OF IDH MUTANT LOWER GRADE GLIOMA USING SPECTROSCOPIC IMAGING OPTIMIZED FOR 2-HYDROXYGLUTARATE DETECTION. (9th November 2020) - LaFontaine, Marisa; Autry, Adam; Philips, Elizabeth; Jalbert, Llewellyn; Villanueva-Meyer, Javier; Chang, Susan; Li, Yan
Abstract: INTRODUCTION: Mutations in isocitrate dehydrogenase (IDH1/2) genes are both diagnostic and prognostic biomarkers for lower grade gliomas, which can be noninvasively evaluated via MRS detection of 2-hydroxyglutarate (2HG). A high percentage of lower grade gliomas harbor IDH mutations that have a major impact on tumor biology. METHODS: Forty IDH-mutant lower grade glioma patients were recruited and scanned using 2HG-optimized 97ms PRESS spectroscopy prior to surgical resection, whereupon image-guided tissue samples were acquired and analyzed via histopathology. Spectra were processed and quantified using LCModel. Wilcoxon ranksum tests were used to compare the difference in metabolic parameters between patient subgroups. Cox proportional hazard models were used to evaluate the influence of metabolic parameters on progression free survival (PFS). Pearson and Kendall Tau rank correlations were used for metabolites and histopathology parameters. RESULTS: Levels of 2HG were quantifiable in 37/40 (92.5%) IDH+ patients, yielding a detection rate of 92.5%. A significant difference in myoinositol/total choline was found between astrocytoma and oligodendroglioma in the newly diagnosed grade II population (N=10/13, p=0.042) and also in the overall population (N=25/15, p=0.022). 2HG/creatine was the only significant prognostic indicator on PFS in newly diagnosed patients (p=0.036, HR=4.435; N=33), who had a median PFS of 1472 days [95%CI 994 1950 days] (15 censored). Significantly decreased glutamate/creatine and increased (2HG+GABA)/creatine (p< 0.0001) were found in the T2 lesion compared to those in the normal appearing white matter. At the location where the biopsy samples were taken, there was a significant relationship between 2HG/creatine and glycine/creatine (0.93±0.01; mean±SD Tau; p=0.0005) as well as 2HG/creatine and glutathione/creatine (0.96±0.02; mean±SD Tau; p=0.001) but no significance between the metabolites and pathology parameters were found. CONCLUSIONS: The non-invasive detection of 2HG can provide clinically relevant information for patient management and our study demonstrated both the feasibility of 2HG detection and its relationship with PFS.